Analisis Hukum Terhadap Pertimbangan Hukum Hakim Yang Menjatuhkan Pidana Pembinaan Terhadap Pelaku Tindak Pidana Narkotika - Benny Nuovandi Butar Butar; Hisar Siregar; Meli Hertati Gultom (Fakultas Hukum Universitas Riau, 2026)
This paper uses a case study of Mataram District Court Decision Number 26/Pid.Sus.Anak/2022/PN.Mtr. to examine the legal factors judges take into account when imposing correctional sentences on juvenile offenders of drug offenses. The research focuses on how the integrated assessment results serve as a foundation for the judge's deliberations, how the restorative justice principle is applied, and how well correctional sentences support child rehabilitation and deter recidivism levels. This study employs a case study methodology in conjunction with a normative juridical legal research method. Primary legal materials, such as court rulings, as well as secondary legal materials, such as laws and regulations, scholarly publications, and pertinent legal literature, were examined in order to gather data for a literature review.The results show that the integrated assessment has a strategic role in helping judges understand the child's condition comprehensively, encompassing legal, medical, psychological, and social aspects. The judge's considerations in the decision are not only based on legal aspects such as evidence and positive legal provisions, but also consider non-legal factors such as the child's psychological condition, family background, and potential for rehabilitation and social reintegration. The application of correctional punishment in this decision reflects the implementation of the principles of the best interests of the child and restorative justice, which prioritize recovery over repressive punishment. Corrective punishment is considered more effective than imprisonment in preventing recidivism and supporting the rehabilitation of child drug abusers, as long as it is supported by optimal rehabilitation and ongoing supervision.